2015
DOI: 10.1021/acs.analchem.5b02746
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Lateral Positioning of Microparticles Inside Droplets Using Acoustophoresis

Abstract: In this paper, we utilise bulk acoustic waves to control the position of microparticles inside droplets in two-phase microfluidic systems and demonstrate a method to enrich the microparticles. In droplet microfluidics different unit operations are combined and integrated on-chip to miniaturise complex biochemical assays. We present a droplet unit operation capable of controlling the position of microparticles during a trident shaped droplet split. An acoustic standing wave field is generated in the microchanne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Of these, acoustophoresis has the advantages of being label free, gentle, and operated in non-contact mode. However, in our previous work, there have been experimental indications that the acoustic particle focusing inside droplets is impaired by a difference in acoustic properties between the droplet and the continuous phase (Fornell et al 2015). Typically, water-based solutions are used as the dispersed phase as living cells are often encapsulated inside the droplets, and fluorinated oils such as Novec HFE-7500 or FC-40 with the addition of fluorosurfactants are used as the continuous phase (also known as the carrier oil).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Of these, acoustophoresis has the advantages of being label free, gentle, and operated in non-contact mode. However, in our previous work, there have been experimental indications that the acoustic particle focusing inside droplets is impaired by a difference in acoustic properties between the droplet and the continuous phase (Fornell et al 2015). Typically, water-based solutions are used as the dispersed phase as living cells are often encapsulated inside the droplets, and fluorinated oils such as Novec HFE-7500 or FC-40 with the addition of fluorosurfactants are used as the continuous phase (also known as the carrier oil).…”
Section: Introductionmentioning
confidence: 96%
“…Recently, acoustic particle manipulation has also been implemented in droplet-based microfluidic systems for manipulation of whole droplets (Schmid et al 2014;Leibacher et al 2015;Sesen et al 2015) and focusing of particles and cells inside droplets (Fornell et al 2015Park et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 The ARF depends on the size, shape, density, and compressibility of the suspended micro-objects, and variations in any of these parameters can be used to distinguish, separate, sort, trap and manipulate microobjects on-demand. 5,6 Most acoustouidics devices, which use bulk acoustic waves (BAWs), [7][8][9][10] Lamb waves (LWs), 11,12 travelling surface acoustic waves (TSAWs) [13][14][15][16][17][18] or standing surface acoustic waves (SSAWs) [19][20][21][22] for the manipulation of microparticles, cells, bacteria, or droplets, depend upon variations in the sizes of the micro-objects. A few studies have reported the use of variations in the intrinsic properties such as the density or compressibility of the micro-objects for their manipulation instead of their sizes.…”
Section: Introductionmentioning
confidence: 99%
“…All of the above-described systems require fabrication or use of an electric or magnetic system on-chip. Some other works have demonstrated separation or enrichment using acoustic waves [27,28] or flow fields [29,30]. …”
Section: Introductionmentioning
confidence: 99%